2003
DOI: 10.1063/1.1615677
|View full text |Cite
|
Sign up to set email alerts
|

Superhard self-lubricating AlMgB14 films for microelectromechanical devices

Abstract: Performance and reliability of microelectromechanical system (MEMS) components can be enhanced dramatically through the incorporation of protective thin-film coatings. Current-generation MEMS devices prepared by the lithographie-galvanoformung-abformung (LIGA) technique employ transition metals such as Ni, Cu, Fe, or alloys thereof, and hence lack stability in oxidizing, corrosive, and/or high-temperature environments. Fabrication of a superhard self-lubricating coating based on a ternary boride compound AlMgB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 23 publications
4
47
0
1
Order By: Relevance
“…Many compounds are known, such as AlMgB 14 , AlNaB 14 , AlLiB 14 , AlYB 14 , AlTbB 14 , AlDyB 14 , AlHoB 14 , AlErB 14 , AlYbB 14 and AlLuB 14 [1][2][3][4][5]. Bulk modulus of AlMgB 14 was measured to be in the range of 196-264 GPa [6]. Kölpin et al performed ab initio calculations on XMgB 14 (X¼ Al, C, Si, Ge, Mg, Sc, Ti, V, Zr, Hf, Nb, Ta) [7] as well as Al x Y y B 14 (x, y¼0.25, 0.5, 0.75, 1.00) [8] and reported bulk moduli in the range from 196 to 228 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many compounds are known, such as AlMgB 14 , AlNaB 14 , AlLiB 14 , AlYB 14 , AlTbB 14 , AlDyB 14 , AlHoB 14 , AlErB 14 , AlYbB 14 and AlLuB 14 [1][2][3][4][5]. Bulk modulus of AlMgB 14 was measured to be in the range of 196-264 GPa [6]. Kölpin et al performed ab initio calculations on XMgB 14 (X¼ Al, C, Si, Ge, Mg, Sc, Ti, V, Zr, Hf, Nb, Ta) [7] as well as Al x Y y B 14 (x, y¼0.25, 0.5, 0.75, 1.00) [8] and reported bulk moduli in the range from 196 to 228 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…AlYB 14 (space group Imma) belongs to a group of boron-rich solids with fascinating properties. Many compounds are known, such as AlMgB 14 , AlNaB 14 , AlLiB 14 , AlYB 14 , AlTbB 14 , AlDyB 14 , AlHoB 14 , AlErB 14 , AlYbB 14 and AlLuB 14 [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…13 XPS also indicated that there is no appreciable difference in composition between room-temperature-and 573 K-deposited AlMgB 14 films. The microstructure of AlMgB 14 films, which was examined by transmission electron microscopy, 12 remains amorphous regardless of substrate temperature, and no evidence of conducting inhomogeneities or crystalline domains was observed.…”
mentioning
confidence: 99%
“…Figure 3 shows the Tauc plots of AlMgB 14 films, from which the optical band gaps are determined to be ϳ0.5 eV, and it appears that the deposition temperature does not have a strong effect on the optical gaps. Therefore, the different carrier concentrations in AlMgB 14 films can only be attributed to the trap states of different characters, i.e., an increase in deposition temperature leads to a higher density of well-formed B 12 icosahedra, 12 which, in turn, gives rise to more electron trap states in the gap. As the density of these trap states increases, a decrease in carrier concentration is expected, which is indeed observed in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation